Current Trends and Future Directions for Geoheritage Assessment Methodology in Morocco - Mustapha El Hamidy; Ezzoura Errami; Aymane Elkaichi (Geoconservation Research)
Inventorying and assessing geoheritage is a prerequisite for developing measures to preserve unique geological and geomorphological sites. Several researchers have developed methods for assessing and determining the value of geological and geomorphological sites. Given rapid environmental and climatic changes, it is crucial to improve the state of geoheritage assessment and inventory development. This overview presents an analysis of research on geoheritage assessment conducted in Morocco over the past 14 years (2008–2022). The objective is to provide an overview of the main methodological approaches. The analysis is based on a search of the Science Direct, Scopus, and Google Scholar databases to identify publications dealing mainly with Moroccan geoheritage sites. We find that most studies have concentrated on the identification and characterization of various geoheritage sites across the country, employing only the descriptive method. However, as the field has progressed, earth scientists are applying quantitative inventory and assessment methods, with some initiatives to propose new methods adapted to the Moroccan context.